Addressing the elephant that's not in the room - Larsen, Matthew David (2011)
The omission of Jesus' death in the Eucharistic prayers in Did. 9-10 presents a quagmire that has generated no dearth of scholarly discussion. This paper addresses the questions: (1) how do these prayers relate to the ritual normally associated with the Last Supper tradition and (2), assuming a date of the final form of the Didache around the end of the 1st century CE, why does the Didachist utilize the Eucharistic prayers found in Did. 9-10 as opposed to the Last Supper tradition? While not dismissing the redactional layering of the Didache, this paper suggests that reading the document as a literary whole bears fruit in this discussion. The Didache, when read as a whole, demonstrates a consistent desire to maintain her/his community within Jewish ritual and social praxis. With this in mind, these prayers in Did. 9-10 seem a logical choice over the Last Supper tradition.